Health Professionals’ Attitudes Towards Mental Illness Patients - Monika Natalia; Suryani Suryani; Imas Rafiyah (Journal of Nursing Care, 2019)
Health workers are people who have knowledge and skills through education and also devoted themselves in the health areas. The attitude of health workers has determined the services to the patient including patients with mental disorders. A negative attitude is one of the elements formed the stigma against ODGJ (mental disorder patients) who is the greatest barrier to the treatment and the development of effective treatments. This study aimed to identify the attitude of health workers to people with mental disorders at Puskesmas Jatinangor.The research used quantitative descriptive with the cross-sectional approach. The research used the technique of total sampling from the population. The sample was all health workers in Puskesmas Jatinangor total of 55 people. Data taken by using the instrument of Mental Illness: Clinician's Attitude Scale (MICA) developed by Gabbidon et al (2013). Data analysis used a descriptive analysis of the attitude in the form of the mean and the presentation. The higher the total score more and showed negative attitudes (stigmatization).The results showed that more than half of the total respondents had a positive attitude tend to value the mean 48.78 ± SD 8.993. This can conclude that health workers in Puskesmas Jatinangor had favored attitudes, accepted, and recognized ODGJ. It is recommended to all health workforce would maintain and increase positive attitudes towards ODGJ.